Bibliografía sobre el plátano (Musa AAB, ABB) - International Network for the Improvement of Banana and Plantain (1992)
A collection of 1944 bibliographical references on plantain covering publications from 1911 to 1992 from 53 countries. The documents were published as articles in specialized journals, books, theses, annual reports, research reports, papers presented at scientific meetings and state-of-the-art reports in various languages including Spanish, English, French and Portuguese. The thematic structure of the bibliography approaches agronomic aspects of plantain such as plant anatomy, genetics and improvement, physiology, cultural practices, pests and diseases, soil, irrigation and drainage and post-harvest handling of fruits. Coverage also includes agro-industry, marketing and socioeconomic aspects of plantain. The references are numbered and author and keyword indexes refer to the numbers. UPEB / INIBAP / IDRC